STRATEGI PEMASARAN DIGITAL KOPERASI SIMPAN PINJAM DALAM UPAYA MENARIK NASABAH PADA CREDIT UNION BAHTERA SEJAHTERA KEWAPANTE - Maria Febiana Kimang; Yustina Olivia da Silva; Elisabet Luju (Universitas Nusa Nipa Maumere, 2026)
KSP Credit Union Bahtera Sejahtera is one of the cooperatives established to advance and improve the welfare of the community or its members in savings and loan activities. The main activities of KSP Credit Union Bahtera Sejahtera are to collect funds from its members in the form of savings and distribute them in the form of loans. This study aims to determine the digital marketing strategy of the savings and loan cooperative in an effort to attract customers at CU Bahtera Sejahtera Kewapante, to find out how the number of members has developed over the past three years, and to understand the role of KSP CU Bahtera Sejahtera Kewapante's management in increasing the number of members. This research uses a qualitative approach with data collection techniques through interviews, documentation, and observation. The results show that the marketing strategy of the savings and loan cooperative focuses on efforts to attract new members by introducing cooperative products directly to the community and through social media. Over the past three years, the number of members at KSP Credit Union Bahtera Sejahtera Kewapante has experienced stagnation or very slow growth. Management plays a very important role in maintaining the sustainability of the cooperative, improving members' welfare, and ensuring the cooperative remains relevant amid economic changes. KSP CU Bahtera Sejahtera faces various obstacles in increasing the number of members, such as lack of effective socialization and promotion, limited resources, negative perceptions of cooperatives, competition from other financial institutions, infrastructure limitations, and dependence on old members. These findings emphasize the importance of improving marketing strategies to increase member growth, enhancing service quality, and building good relationships with the community.